Conceptualizing A-HERO for sport employees' well-being. Issue 4 (9th September 2019) - Oja, Brent D.; Kim, Minjung; Perrewé, Pamela L.; Anagnostopoulos, Christos
Abstract : Purpose: In an attempt to promote sport employees' well-being, the purpose of this paper is to examine the more traditional constructs of psychological capital (i.e. hope, efficacy, resiliency and optimism) and to feature the inclusion of authenticity, an often overlooked construct, among sport employees. Design/methodology/approach: This conceptual paper is designed to create an expanded sport employee psychological capital construct, labeled A-HERO, and a subsequent theoretical model to improve their well-being. Findings: In detailing a conceptual model of A-HERO for well-being, the model includes and explains the relationships among sport employee antecedents (i.e. sport employee identification, pride and passion), an organizational contextual variable (person–organization fit), and an important employee and organizational outcome (i.e. employee well-being) in contemporary sport organizations. Research limitations/implications: A-HERO offers a necessary first step for future theoretical research and empirical applications to improve sport employees' well-being. Originality/value: By elucidating the role of authenticity at work with traditional psychological capital constructs in the current sport industry, this paper stimulates sport business and management scholars to validate empirically the A-HERO construct and examine proposed relationships for an improved prediction of sport employees' well-being.